Procalcitonin levels in children aged 3-36 months with suspected serious bacterial infection - Tuty Herawaty; Alan R. Tumbelaka; Dwi Putro Widodo; Partini Pudjiastuti Trihono; Darmawan B. Setyanto; Piprim B. Yanuarso (Indonesian Pediatric Society, 2010)
Background Fever in children aged 3-36 months is usually caused by viral infection, however, 11-20% of cases may progress into serious bacterial infection (SBI). A good diagnostic tool is required to detect SBI to reduce mortality and avoid unnecessary use of antibiotics.Objectives To determine procaldtonin (peT) levels, and etiology of bacteremia in febrile children aged 3-36 months old with suspected SBI.Methods A cross-sectional descriptive study was conducted in Cipto Mangunkusumo and Tangerang General Hospital during April-May 2010. Complete blood cells count and acute illness observation score (AIOS) were perfonned on febrile children aged 3-36 months. Subjects meeting the inclusion criteria underwent blood culturing and testing of procalcitonin levels.Results There were 39 children met the criteria. Boys and girls ratio was 1.6 Mth median age of 10 months. Mean of AlOS was 20.5 (4.5 SD) and mean of hemoglobin was 10.2 (SD 2.1) g/dL. Median of leukocyte and absolute neutrophyl count were 18,600/uL and 12,300/uL, respectively. Median of procaldtonin 1.8 (range 0.04-71.60) ng/mL, mean of procalc itonin in bacteremia subgroup 22.60 (SD 27.6) ng/mL and 6.38 in non-bacteremia subgroup (11.0 SB) ng/mL. In children with severely ill appearance, the likelihood of procaldtonin levels ≥2 ng/mL was 8.67 times higher (95%CI 1.66 to 50.56) than in moderately or mildly ill-appearing children. In subjects Mth procalcitonin level of ≥2 ng/mL, the risk of bacteremia was 8.1 times (95% CI 2.9 to 1051.6) higher and the risk of sepsis was 55.47 times higher than in subjects Mth procalcitonin <2 ng/mL (95% CI 1.22 to 68.02). We observed bacteriemia in 11 of 39 subjects (28.2%). The pathogens isolated from these 11 subjects were Klebsiella pneumonia, Staphylococcus aureus, Eschericia coli, Serratia marcesens, Staphylococrus saprophyticus, and Serratia liqueafaciens.Conclusion The proportion of bacteremia in children aged 3-36 months old with suspected serious bacterial infection was 28.2% with no predominant microorganism. Elevated procaldtonin level of ≥ 2 ng/mL was assodated with severe illness apppearance, bacteremia, and sepsis.